Achieving Universal Health Coverage through Voluntary Insurance : What Can We Learn from the Experience of Lao PDR? - Alkenbrack, Sarah; Jacobs, Bart; Lindelow, Magnus (BioMed Central, 2015)
The Government of Lao Peoples’ Democratic Republic (Lao PDR) has embarked on a path to achieve universal health coverage (UHC) through implementation of four risk-protection schemes. One of these schemes is community-based health insurance (CBHI) – a voluntary scheme that targets roughly half the population. However, after 12 years of implementation, coverage through CBHI remains very low. Increasing coverage of the scheme would require expansion to households in both villages where CBHI is currently operating, and new geographic areas. In this study we explore the prospects of both types of expansion by examining household and district level data.